2020
DOI: 10.1177/1971400920980311
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging analysis in scrub typhus meningoencephalitis to determine the alteration of microstructural subcortical white-matter integrity

Abstract: Background and purpose Magnetic resonance imaging (MRI) of the brain in scrub typhus meningoencephalitis is non-specific, and in the majority of the cases, conventional MRI fails to detect any abnormality. However, autopsy reports depict central nervous system involvement in almost all patients. There is therefore a need for research on the quantitative assessment of brain parenchyma that can detect microstructural abnormalities. The study aimed to assess the microstructural integrity changes of scrub typhus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Conventional neuroimaging may show non-specific findings in scrub typhus meningoencephalitis. A study based on diffuse tensor imaging by Phukan et al revealed alteration of subcortical white-matter integrity in scrub typhus meningoencephalitis representing axonal degeneration and myelin breakdown [ 17 ]. CSF analysis in scrub typhus meningoencephalitis is distinct from bacterial meningitis, as lymphocytic pleocytosis is not seen in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional neuroimaging may show non-specific findings in scrub typhus meningoencephalitis. A study based on diffuse tensor imaging by Phukan et al revealed alteration of subcortical white-matter integrity in scrub typhus meningoencephalitis representing axonal degeneration and myelin breakdown [ 17 ]. CSF analysis in scrub typhus meningoencephalitis is distinct from bacterial meningitis, as lymphocytic pleocytosis is not seen in the latter.…”
Section: Discussionmentioning
confidence: 99%